Dendritic Cell Subsets in Asthma: Impaired Tolerance or Exaggerated Inflammation? - Vroman, Heleen; Hendriks, Rudi W.; Kool, Mirjam (Frontiers in Immunology, 2017)
Asthma is a prevalent chronic heterogeneous inflammatory disease of the airways, leading to reversible airway obstruction, in which various inflammatory responses can be observed. Mild to moderate asthma patients often present with a Th2-mediated eosinophilic inflammation whereas in severe asthma patients, a Th17-associated neutrophilic or combined Th2 and Th17-mediated eosinophilic/neutrophilic inflammation is observed. The differentiation of these effector Th2 and Th17-cells is induced by allergen exposed dendritic cells (DCs) that migrate towards the lung draining lymph node. The DC lineage comprises conventional DCs (cDCs) and plasmacytoid DCs (pDCs), of which the cDC lineage consists of type 1 cDCs (cDC1s) and cDC2s. During inflammation, also monocytes can differentiate into so-called monocyte-derived DCs (moDCs). These DC subsets differ both in ontogeny, localization, and in their functional properties. New identification tools and the availability of transgenic mice targeting specific DC subsets, enable the investigation of how these different DC subsets contribute to or suppress asthma pathogenesis. In this review, we will discuss mechanisms used by different DC subsets to elicit or hamper the pathogenesis of both Th2-mediated eosinophilic asthma and more severe Th17-mediated neutrophilic inflammation.